The Invisible Struggle: Impact of COVID-19 and Digital Inequality on Students’ Mental Well-Being - Henry Sevilla-Morales (IAFOR Journal of Education)
This phenomenological study sought to understand the lived experiences of socially disadvantaged students from the Universidad Nacional, Costa Rica, who faced digital inequality during emergency remote education amid the COVID-19 pandemic, as well as their challenges vis-à-vis the transition to in-person classes in 2022. Using a hermeneutic phenomenological design, data were collected through semi-structured and focus-group interviews with five EFL students from two TESOL programs. The data analysis followed Colaizzi’s (1978) model, a multi-step process that includes extracting significant statements, formulating meanings, organizing them into categories and themes, and validating results through member checks. Findings assist an understanding of the complex impact of digital inequality on the mental health of socially disadvantaged students and the transition back to in-person classes. The research proves not only significant but also vital since it sheds light on the lived experiences of learners amidst an event whose psychological toll is yet to be fully comprehended.